REPUBLIC FAR AWAY WITHIN THE TERRITORIES FARMING ON THEIR FARMS SMART IRRIGATION SYSTEM AND HER STRUCTURE ALGORITHM BLOCK SCHEME - Jamoljon Djumanov; Abdurazzokov Jamshid (Modern American Journals, 2025)
This article Arduino microcontroller and many devices (humidity, temperature, pressure) and water flow using sensors smart irrigation system how to build explains. Our irrigation system of the soil water balance of determination clear method automatic accordingly unites water in the content to vibrations answer. So this how as better our work possible is an example of measurements accuracy increase, maybe decisions automation through irrigation systems.